Accounting Management According to the Requirements of International Standards in Lithuania - Lakis, Vaclovas (Ekonomika, 1998)
Problems of accounting management have two aspects: technical and economic. The technique of accounting management could be changed and improved easily. The use of computer and other organisational techniques made great influence on the improvement of the accounting management technique.The economic aspect of accounting management depends on laws and economic reality. Since different countries developed dissimilarly, the accounting also became different. It is more similar in those groups of countries that had interrelations. This is how so called bookkeeping models were formed.Seeking to harmonise accounting and financial statement on a world scale and this way to facilitate the economic co-operation among countries, International standards of accounting were determined, and on a European Union scale - Directives.Lithuania from the very beginning of independend accounting management expressed intention to manage it according to the requirements of international standards. The article analyses the problems that have to be solved, and imperfections that have to be eliminated that accounting would correspond with the requirements of international standards. Noteworthy, improwing bookkeep and financial statement, attention should be paid not only to the Directives of the European Union but also to the International standards of accounting requirements.